Influence Of Product Quality On Repurchase Intention Mediated By Customer Satisfaction On Sunscreen Products In Cimahi City - Syaputri, Delya Rubi; Herawati, Siti (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the effect of product quality on repurchase intention with customer satisfaction as a mediating variable in the context of the highly competitive sunscreen market. Methodology: The research employs a quantitative approach with an explanatory design. Data were collected through structured questionnaires from 120 users of Nivea Sunscreen in Cimahi City selected using purposive sampling. The data were analyzed using simple and multiple linear regression, supported by the Sobel mediation test. Results: The results reveal that product quality significantly affects customer satisfaction (Î² = 0.428; p < 0.05) and repurchase intention (Î² = 0.269; p < 0.05), while customer satisfaction also significantly influences repurchase intention (Î² = 0.465; p < 0.05). The Sobel test confirms that customer satisfaction significantly mediates the relationship between product quality and repurchase intention (t = 4.95; p < 0.001). The results indicate that product quality has a significant positive effect on customer satisfaction and repurchase intention, while customer satisfaction also significantly influences repurchase intention. The Sobel test confirms that customer satisfaction significantly mediates the relationship between product quality and repurchase intention. Novelty: This study highlights the mediating role of customer satisfaction in explaining repurchase behavior within the sunscreen product category. Findings: Customer satisfaction strengthens the impact of product quality on repurchase intention, reinforcing the relevance of Expectancy-Disconfirmation Theory and the Theory of Planned Behavior. Originality: The originality of this study lies in its empirical evidence from a saturated cosmetic market, focusing on sunscreen products and mediation analysis. Conclusions: Enhancing product quality is essential to increasing customer satisfaction, which subsequently drives consumer loyalty and repeat purchases. Type of Paper: Empirical Quantitative Research Paper.